ANALYZING THE IMPACT OF EMPLOYEES' ORGANIZATIONAL SUPPORT AND HAPPINESS IN THE WORKPLACE ON INNOVATIVE WORK BEHAVIOR AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR: THE MEDIATING ROLE OF ORGANIZATIONAL COMMITMENT - Liqaa Mutter Atti; Samir Hasan Abdulhussein (American Journals, 2023)
The purpose of this research is to analyze the effect of organizational support of employees and happiness in the work environment on innovative work behavior and organizational citizenship behavior: the mediating role of organizational commitment. In terms of the nature of the research, the present research is descriptive and in terms of the purpose of the research, it is a part of applied research. Statistical population in this research the statistical population in this research is the faculty members of The Southern Technical University in Iraq, whose number was equal to 315 people. In this research, Cochran's formula was used to calculate the sample size. The number of samples was equal to 173. The obtained results confirmed all research hypotheses.
Keywords: Organizational behavior, organizational commitment, employee support, and citizenship behavior